Royal Australasian College of Surgeons Rural Health Equity Strategic Action Plan: excellence through equity. Issue 9 (5th August 2022) - Clancy, Bridget
Abstract: Wherever there are people there will be a need for surgical care. Rural people have all kinds of problems and need all kinds of surgeons. The Royal Australasian College of Surgeons (RACS) Rural Health Equity Strategic Action Plan (RHESAP) was endorsed by Council in December 2020. The goal is to increase the rural surgical workforce and increase access to care, through providing motivated surgeons with the training they need to work where they are needed most. The Royal Australasian College of Surgeons Surgical Education and Training Programs (SET) aim to train generalist surgeons across all nine surgical disciplines. To increase the rural surgical workforce and increase access to care, we need to select for rural origin, rural medical school and rural work experience, provide all trainees with the opportunity for positive rural work exposure with an aligned rural curriculum, and we need to support surgeons already living and working in rural areas. In future, with persistent health inequity for underserved populations and the impacts of climate change, we anticipate an increasing need for a culturally and emotionally intelligent, broad‐scope surgical workforce, across all surgical disciplines, with the skills, confidence and motivation to work collaboratively and effectively in surgical teams, in areas of need and limited resource environments, including globally. Abstract : Wherever there are people there will be a need for surgical care. Rural people have all kinds of problems and need all kinds of surgeons. The Royal Australasian College of Surgeons (RACS) Rural Health Equity Strategic Action Plan (RHESAP) was endorsed by Council in December 2020. The goal is to increase the rural surgical workforce and increase access to care, through providing motivated surgeons with the training they need to work where they are needed most.